On the extension of even-positive-definite functions of one and two variables - Lopotko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove theorems on the extension of even-positive-definite functions from a finite interval to the entire axis and from a strip onto the entire plane.